2016
DOI: 10.1371/journal.pone.0162475
|View full text |Cite
|
Sign up to set email alerts
|

Protein Restriction with Amino Acid-Balanced Diets Shrinks Circulating Pool Size of Amino Acid by Decreasing Expression of Specific Transporters in the Small Intestine

Abstract: Dietary protein restriction is not only beneficial to health and longevity in humans, but also protects against air pollution and minimizes feeding cost in livestock production. However, its impact on amino acid (AA) absorption and metabolism is not quite understood. Therefore, the study aimed to explore the effect of protein restriction on nitrogen balance, circulating AA pool size, and AA absorption using a pig model. In Exp.1, 72 gilts weighting 29.9 ± 1.5 kg were allocated to 1 of the 3 diets containing 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 60 publications
2
23
0
Order By: Relevance
“…Even when an adequate amount of calories is supplied in the blood, as for instance with parenteral nutrition, morphological and functional alterations of the small intestine mucosa are observed; the small intestine absorptive surface area appears to be reduced because of a decrease in cell proliferation, differentiation, and migration along the crypt-to-villi axis. That luminal amino acid availability also affects intestinal amino acid transporter expression has been shown in different animal models (2,20,27,28). In our study, we observed a reduction in cryptal cell proliferation in the intestinal area distal to the obstruction not receiving amniotic fluid.…”
Section: Discussionsupporting
confidence: 76%
“…Even when an adequate amount of calories is supplied in the blood, as for instance with parenteral nutrition, morphological and functional alterations of the small intestine mucosa are observed; the small intestine absorptive surface area appears to be reduced because of a decrease in cell proliferation, differentiation, and migration along the crypt-to-villi axis. That luminal amino acid availability also affects intestinal amino acid transporter expression has been shown in different animal models (2,20,27,28). In our study, we observed a reduction in cryptal cell proliferation in the intestinal area distal to the obstruction not receiving amniotic fluid.…”
Section: Discussionsupporting
confidence: 76%
“…Most previous studies focused on extremely protein restrictive diets, in which protein levels were reduced by about 60–100%, or on specific essential amino acid (EAA), such as methionine and branched‐chain AA, which were restricted by 50% or more, far below the estimated average requirement for human and rodents, likely unsustainable and unhealthy due to the severe deficiency of EAA . We demonstrated that moderate PR diets, whose protein levels were reduced by about 20%, shrank circulating AA pool size and profoundly altered the pathways concerning immune function in the small intestine even with the supplementation of crystal EAA in diets . However, the impact of moderate PR without malnutrition on insulin resistance remains unclear.…”
Section: Introductionmentioning
confidence: 85%
“…In Experiment 3, 12, 60 days old, castrated male growing pigs ( n = 6) with 22.7 ± 1.3 kg BW were housed individually. After 3 days of adaption, pigs were equipped with catheters in portal vein and cared as described previously . Subsequently, pigs were pair‐fed the same amount of the control (18% CP) and moderate PR diet (14% CP), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Protein expression levels of TLR4, MyD88, NF-κB, TNF-α, IL-1β, occludin, zonula occludens-2 (ZO-2) and P38 in both jejunal and ileal mucosa were measured by Western blot (21) and normalised by the protein expression of β-actin. Briefly, about 100 mg of frozen jejunal or ileal mucosa were powdered in liquid nitrogen and lysed in RIPA buffer containing 50 mM Tris-HCl (pH 7•4), 150 mM NaCl, 1 % NP-40 and 0•1 % SDS, plus a Halt protease inhibitor cocktail (Thermo Fisher Scientific).…”
Section: Western Blot Analysismentioning
confidence: 99%